Parents’ influence and conduct in U15’s football - Pulido Salas, D.; Borrás Rotger, P. A.; Ponseti Verdaguer, F. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
In this investigation is analysed the influence and the conduct carried out by footballers’ parents who belong to 2nd category of U15’s league in the Balearic Islands. This study is focused on management behaviours, pressure, support, comprehension and parents’ active participation. The participants were 102 parents (63 fathers and 39 mothers) who participated voluntarily with the study during the 2016-2017 season filling up the questionnaire Análisis del Comportamiento y Actuación de Padres y Madres en el Deporte (ACAPMD). Furthermore, 176 young footballers filled up the questionnaire Parental Involvement Sports Questionnaire (PISQ). The results show that, firstly, doesn’t exist significant differences between obtained data by fathers and mothers. Results also point that parents have high implication levels about their children’s sport. Furthermore, parents are interested into keep a nice parent-child relationship and they value positively their sons’ sportive schools. On the other hand, parents don’t agree with spectators’ interventions from the grandstands in their children’s matches.